2022
DOI: 10.1021/acsaelm.2c00623
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Mechanical Properties of Free-Standing SiNx Thin Films Depending on PECVD Conditions for Controlling Residual Stress

Abstract: Silicon nitride (SiN x ) thin films are crucial in electronic devices and are used as gate dielectrics and diffusion barriers for thin-film transistors (TFTs). Plasma-enhanced chemical vapor deposition (PECVD) has been used for the deposition of SiN x thin films because it allows the tuning of the properties of SiN x thin films by changing the deposition conditions depending on their usage. However, the intrinsic mechanical properties of SiN x thin films depending on the PECVD conditions have rarely been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Additionally, the effect of residual stress was excluded because the IAI thin films on the water surface could freely release the substrate constraint. 33 Moreover, the effect of surface roughness was negligible because there was no significant difference in root mean square roughness ( R q ) with respect to the Ag interlayer thickness (Fig. S5, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the effect of residual stress was excluded because the IAI thin films on the water surface could freely release the substrate constraint. 33 Moreover, the effect of surface roughness was negligible because there was no significant difference in root mean square roughness ( R q ) with respect to the Ag interlayer thickness (Fig. S5, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…ALD Al 2 O 3 films after exposure to a hygrothermal environment can be considered bilayers composed of degraded and pure ALD Al 2 O 3 . The E values of the bilayer thin films were calculated using eqn (1), which is a method of approach to approximate estimation of composite material properties, called the rule of mixture: 35–37 E b = E u *( t u / t b ) + E d *( t d / t b ) ≈ E u …”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the mechanical reliability of ceramics is highly dependent on surface conditions, such as cracks, pores, flaws, residual stress, and surface roughness. 38,39 Previous studies have reported that the e and S of brittle materials such as Al 2 O 3 are improved with decreased surface roughness. 38,40 Cheng et al conducted a digital image correlation analysis and showed a recognizable stress concentration at the valleys of a rough surface, where the stress concentration was induced around the pores, reducing S and e. 41 In addition, the interaction between the pores and other defects, such as pores and cracks, can affect the stress concentration and risk of crack propagation.…”
Section: Characterization Of the Hygrothermal Degradation Of Mechanic...mentioning
confidence: 99%
“…It is worth noting that excessive tensile residual stress can result in selfcracking during the delamination of the thin film, making it challenging to accurately measure its mechanical properties. 27 Lastly, the dielectric constant of the TEOS-SiO 2 film was explored to gain insights into the changes in mechanical properties. The dielectric constant is a coefficient related to the material's porosity 28,29 and has a positive correlation with Young's modulus.…”
Section: ■ Discussionmentioning
confidence: 99%